Estudo de pontos quânticos semicondutores e semimagnéticos - Freitas Neto, Ernesto Soares de (2013)
In this work we have employed the Melting-Nucleation method in order to synthesize semiconductor and semimagnetic quantum dots (QDs), CdSe, CdSxSe1-x, CdS e Cd1-xMnxS, in a glass matrix. We have investigated these QDs by using several experimental techniques and theoretical models, reaching a comprehensive understanding of their fundamental properties. The lattice contraction in CdSe QDs was confirmed by Raman spectroscopy, evidencing that the glass matrix (host material) plays an important role on the vibrational modes of nanocrystals (NCs). Advancement in the synthesis of pseudo-bynary CdSxSe1-x QDs was achieved by obtaining a good control on the alloy composition in two variants of precursor dopings, while the QD size is tuned by annealing. Resonant Raman spectra of these CdSxSe1-x QDs were very well described by the continuum lattice dynamics model, suggesting the propagation of optical phonons within the NC. By studying CdS QDs by temperaturedependent Raman spectroscopy, we have demonstrated that there is a large difference between the thermal expansion coefficients of QD e of bulk material. The same conclusions were obtained for the modal Grüneisen parameters and for the anharmonicity coupling constants, so that they have to be estimated independently of bulk parameters in the study of thermal properties of QDs. We have employed the Electron Paramagnetic Resonance in order to confirm that the migration of Mn2+ ions in Cd1-xMnxS NCs, from the core to the surface, can be controlled by a thermal annealing. We have proved yet that the luminescence emitted by Cd1-xMnxS NCs can be controlled by changing the x concentration and by the thermal annealing, in which the emission of Mn2+ ions (4T1 6A1) is only observed when this magnetic impurity is substitutionally into the core of Cd1-xMnxS NC. From temperature-dependent photoluminescence measurements, we have come up with a model based on rate equations that describes well the energy transfers involving two coupled groups of Cd1-xMnxS NPs. Further emissions from deep defect levels were attributed to two energetically different divacancies, VCd VS, in the wurtzite structure of Cd1-xMnxS NPs, which can be controlled by the magnetic doping. By studying the magneto-optical properties of Cd1-xMnxS NPs, we have demonstrated that the self-purification is the dominant mechanism controlling the doping process in semiconductor QDs grown by the melting-nucleation method. We have demonstrated that the multiphonon Raman scattering in the coupled Cd1-xMnxS NPs, as well as the coupling strength between electrons and optical phonons, can satisfactorily be tuned by the magnetic doping with Mn2+ ions and by an appropriate thermal annealing. Furthermore, we have verified that the magnetic doping have induced variations on the sp-d exchange interaction and in the crystalline quality of NPs.